Anti-HIV Passive Immunization: New Weapons in the Arsenal - Ruprecht, Ruth M. (Trends Microbiol, 2017)
Anti-HIV passive immunization with human neutralizing monoclonal antibodies (nmAbs) has made exciting gains: (i) identification of the HIV envelope V2 apex as a new in vivo protective epitope, (ii) a novel clade C SHIV for challenge studies, and (iii) a highly protective, trispecific nmAb. Potent, broad-spectrum protection by nmAbs holds promise.